In vitro Anti-Proliferative and Antioxidant Activities of Stem Extracts of Pereskia bleo (Kunth) DC (Cactaceae) - Hong, Lim Lee; Hui, Meng Er; Radhakrishnan, Ammu Kutty (Malaysian Journal of Science, 2009)
Pereskia bleo (Kunth) DC (Cactaceae) (Pereskia bleo) is a tropical plant that has been reported to possess cytotoxic acitivity against several human cancer cell lines. This study was carried out to investigate the in vitro anti-proliferative and antioxidant activities of the stem extracts of the plant. All extracts did not show significant anti-proliferative activity in both normal mouse fibroblast (NIH/3T3) and mouse mammary cancer (4T1) cell lines. There was an increased rate of proliferation when the 4T1 cells were co-cultured with these extracts under certain conditions. Among the extracts, the t-butanol extract had the highest antioxidant property. All the extracts had the ability to protect normal mouse fibroblast cells against natural and oxidant-induced cell death by apoptosis. Pereskia bleo (Kunth) DC (Cactaceae) (Pereskia bleo) ialah sejenis tumbuhan tropika yang dilaporkan mengandungi aktiviti sitotoksik terhadap beberapa jenis sel kanser manusia. Pengajian ini dijalankan untuk memeriksa aktiviti anti-proliferatif dan anti-oksidan dalam ekstrak-ekstrak dari batang tumbuhan ini. Kesemua ekstrak yang dikajikan tidak mempunyai aktiviti anti-proliferatif yang signifikan terhadap sel jenis normal mouse fibroblast (NIH/3T3) dan mouse mammary cancer (4T1). Kadar proliferasi sel 4T1 bertambah apabila ianya dikultur dengan ekstrak-ekstrak ini di bawah keadaan yang tertentu. Di antara ekstrak-ekstrak ini, ekstrak dari t- butanol mempunyai aktiviti anti-oksidan yang tertinggi. Kesemua ekstrak ini boleh mempertahankan sel NIH/3T3 daripada kematian apoptosis yang berlaku secara semulajadi atau diakibatkan oleh bahan oksidan